Analisis Indeks Aksesbilitas Transportasi Kabupaten/Kota Di Provinsi Kalimantan Timur - Sonny, Imam (Warta Penelitian Perhubungan, 2010)
Province which have a high Native Revenue (PAD) have the tendency to give a very largeportion budget to infrastructures, including to develop facilities and access roads, ports andairports. However, infrastructure facility development has not been based on considerationsof effectiveness and efficiency. There are many governments in the provinces build the airportbased on calculation of profits on paper only without regarding and go along withSpatial Planning District (RTRWK) and Regional Transport Order (Tatrawil) and Local TransportOrder (Tatralok). This study is to assess for infrastructure accessibility index associatedwith spatial transport in the district or city in the province of East Kalimantan, therefore wecan found out which areas has a low value index of accessibility and the necessity to reformand develop the infrastructure. Based on these results, the cities has good cathegory index areSamarinda (29), Balikpapan (1.84), North Penajam Pa5er (13) and Kutai Kartanegara (1.29).It can be seen based in the pattern in which the district / city near PKN has high score.Keywords: index, accessibility, infrastructure transportation